A A COMPARATIVE REVIEW AND NOVEL DESIGN POSSIBILITIES ON SOLAR-DRIVEN ABSORPTION LIBR-H2O REFRIGERATION SYSTEM - Gunawan, Sonix; Arfianto, Widi; Heryadi, Budi (Mesin, 2024)
Solar energy is a promising source of energy because of its potential due to the reduction usage of non-renewable energy. As the demand for cooling increases, solar-powered cooling technologies are becoming increasingly promising. Among the different solar cooling systems, LiBr-H2O absorption chillers are commonly used due to their advantages over NH3-H2O systems. Multiple cycle LiBr-H2O chillers can be powered by easily available flat-plate, evacuated tubular or parabolic solar collectors. This paper reviews Theoretical Principles-Based Analysis and Simulations of solar LiBr-H2O absorption cooling systems, performance comparison of each types and introduces new design options related to auxiliary energy systems and cooling mode cycle. The paper also summarizes other main types of solar absorption cooling systems, including double-effect, half-effect, triple effect and give updates of new technology design of hybrid effect. The choice of water-cooled or air-cooled absorption refrigeration depends on the local climate and water availability. Recent advances have made air-cooled absorption refrigeration a viable option, with comparable COP to water-cooled systems and lower maintenance requirements. Additionally, geothermal heat rejection with low pressure drops can further reduce energy consumption. Solar-powered double-effect absorption cooling systems are recommended for buildings with high cooling loads, while half-effect are suitable for air-cooled solar absorption cooling systems in hot and dry regions with limited water. This paper is specifically intended for those interested in developing solar-driven LiBr-H2O absorption chillers, emphasizing the importance of establishing standardized design guidelines to specific regions and climates in order to promote and expand the usage of solar cooling systems.